The Effect of Brand Image and Promotion on Buying Interest at the Akhwat Sewing House Store, Sidenreng Rappang Regency - Amelia, Putri; Niswaty, Risma; Kasmita, Maya; Syarifuddin, Syarifuddin (Jurnal Administrasi Bisnis, 2025)
The Influence of Brand Image and Promotion on Purchase Interest at the Akhwat Sewing House Store in Sidenreng RappangRegency. Thesis. Business Administration Study Program. Administration Science Department. Faculty of Social Science. Makassar State University. (supervised by Mrs. Risma Niswaty and Maya Kasmita).This study aims to determine the influence of brand image and promotion on purchase intention at akhwat sewing house shops in Sidenreng Rappang Regency. To achieve the goal, the researchers used indicators to measure these variables. The brand image indicators include the superiority of brand associations, the strength of brand associations, and the uniqueness of brand associations. Indicators include advertising promotions, sales promotions, public relations, personal selling and direct marketing. Indicators of buying interest include transactional interest, referential interest, preferential interest, and explorative interest. The research method used is a quantitative method. The sample used is the collection of sample data, namely questionnaires that are tested for validity and reliability tests. The data obtained were processed using data analysis using the SPSS vaersi 25 program which consisted of data normality tests, multiple linear regression analysis, t tests, f tests and the coefficient of determinant R2. The results showed that the brand image variable had a very significant effect on both the buying interest variable. The influence variable has a very good significant effect on the purchase intention variable. The results showed that the brand image and promotion variables had a significant effect partially and simultaneously on the variable of customer buying interest at the Akhwat Sewing House shop in Sidenreng Rappang District, this was proven by the t test and F test. The results of the determinant coefficient showed that brand image and promotion had a large effect 56% of interest in buying at the Sewing Akhwat home shop in Sidenreng Rappang Regency. Keywords: Brand Image, Promotion, Purchase Intention